Studies in Australian Katydids: A Review of the Australian Snub-nosed Sylvan katydids (Tettigoniidae; Pseudophyllinae; Simoderini) - Rentz, Dcf; Su, You Ning; Ueshima, Norihiro (Zootaxa, 2015)
The Australian members of the simoderine katydids are reviewed. The tribe is known from nine genera, five of which occur only in Madagascar, the others are Australian: Chloracantha Hebard (C. lampra, C. angularis sp. nov., C. garradunga sp. nov., C. hilleri sp. nov.), Tallebudgeroptera gen. nov. (T. spininota sp. nov.), Mastigaphoides Weidner (M. haffneri, M. tuberculatus sp. nov., M. vaginalis sp. nov., M. lewisensis sp. nov.), Narea Walker (N. compacta, N. elongata, N. kungaree sp. nov.). Mastighapha Karsch is synonymised with Narea. Descriptions, illustrations, sound recording information and distribution maps are presented for all species.